Properties of Concrete Prepared with Silane Coupling Agent-Impregnated Coral Aggregate and Coral Concrete - Jinming Liu (MDPI AG, 2021)
Silane coupling agent (SCA), a kind of organic solvent, was introduced to improve the performance of coral coarse aggregates and enhance the interfacial adhesion between the inorganic coral aggregate and the cement paste of coral concrete. The crushing indicator and water absorption of the coral aggregates over various dipping times were measured, and the slump, interface microhardness, and compressive strength of coral concrete tested. The microscopic appearances of the coral concrete before and after modification were analyzed based on SEM images. The experimental results indicate that SCA can effectively reduce the crushing indicator and water absorption of coral coarse aggregates, and the modification performance becomes better over time. SCA facilitates the generation of chemical forces between the coral aggregates and cement mortars, improves adhesion between the aggregates and mortars, augments the microhardness of the interface, and increases the compressive strength. According to the microscopic appearance of the treated and untreated coral aggregate interfaces, the aggregates and the mortars are in closer combination after modification.